1985
DOI: 10.1136/bjsm.19.3.138
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of plasma volume changes during marathon running.

Abstract: Indices of fluid loss have been compared in 47 male runners who completed a competitive marathon (42.2 km) race in times varying from 2 hr 37 min to 4 hr 51 min. Body weight was recorded before and after the race; venous blood samples were collected shortly before and immediately after the race and used for the estimation of haemoglobin concentration, packed cell volume and serum concentration of albumin and total protein. All runners drank a total of 1.4 L of water during the race. The mean decrease in body w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

1988
1988
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 11 publications
3
33
0
Order By: Relevance
“…During a marathon, however, plasma volume decreased (Maughan et al 1985;Whithing et al 1984), as has also been found in an ultra-marathon over 67 km (Rehrer et al 1992). In longer ultra-endurance races, however, plasma volume increased Stuempfle et al 2003).…”
Section: Discussionmentioning
confidence: 54%
“…During a marathon, however, plasma volume decreased (Maughan et al 1985;Whithing et al 1984), as has also been found in an ultra-marathon over 67 km (Rehrer et al 1992). In longer ultra-endurance races, however, plasma volume increased Stuempfle et al 2003).…”
Section: Discussionmentioning
confidence: 54%
“…Transient expansion of plasma volume commonly is reported after endurance events (Fellmann 1992;Fellmann et al 1999;Maughan et al 1985;Milledge et al 1982). Probably plasma volume seems to behave differently after longer distances.…”
Section: Change Of Plasma Volume Due To Hormonal Changes?mentioning
confidence: 94%
“…An increase of plasma protein-especially albumin-might explain an increase in plasma volume. Maughan et al (1985) found after a marathon an increase of total protein and albumin as well as Mischler et al (2003) after a multistage ultraendurance trial. Mischler et al (2003) detected an increased albumin synthesis after day 4 of exercise by 15%, whereas protein concentration was decreased by 8% after the same day.…”
Section: Increased Protein Synthesis and Increase Of Plasma Volume?mentioning
confidence: 96%
“…However, it is well-established that thirst perception is an insufficient means to match fluid losses during exercise. 28 In addition, a body mass reduction of 3% or even less during 16 km of walking or running under the extreme environmental condition of heat stress 29 or during a marathon 30 has been associated with a decrease in plasma volume. These studies suggest that restoration of fluids lost via sweating should be promoted during prolonged, moderate-intensity exercise in the heat to ensure cardiovascular and thermoregulatory stability.…”
Section: Discussionmentioning
confidence: 99%